G71 Assessing the impacts from the first year of rotavirus vaccination in the uk. (27th April 2015) - Marlow, RD; Muir, P; Vipond, I; Trotter, CL; Finn, A
Abstract : Aims: The United Kingdom added rotavirus vaccine (Rotarix GlaxoSmithKline) to the national immunisation schedule in July 2013. We have performed two years of active surveillance at our regional children's hospital to establish the baseline characteristics of disease burden pre-rotavirus vaccine and now report the epidemiological trends one year after vaccine introduction. Methods: During the 2012–2014 rotavirus seasons, children presenting to our regional paediatric emergency department with gastroenteritis symptoms (>2 loose stools and/or >1 episode of forceful vomiting in the last 24 h) had stool virology analysis (real-time PCR), severity assessment (Vesikari score) and clinical outcome recorded. Nosocomial cases were retrospectively identified as patients admitted with a non-gastroenteritis diagnosis testing positive for rotavirus more than 48 h after admission. Results: In comparison to the pre-vaccine seasons, in the first year after vaccine introduction there were 42–47% (p < 0.001) fewer attendances diagnosed with gastroenteritis, a 38–58% (p < 0.001) reduction in gastroenteritis admissions and a total saving of 300–358 bed days occupancy. Overall there was a 73–78% reduction in number of stool samples testing positive for rotavirus. In those under 1 year old there was a 94% reduction in rotavirus positive cases and a 67–70% reduction in those too old to have been vaccinated (1–4 years). Conclusions: In the first year after the introduction of universal vaccination against rotavirus we observed a profound reduction in gastroenteritis presentations and admissions and a fall in overall seasonal workload. Although by early 2014 only those under 1 year old had been vaccinated, there was also a significant herd effect with many fewer cases than expected in older children. Extrapolating these findings to the UK population we estimate secondary healthcare savings in the first year of ≈£7.5 million. Ongoing surveillance will be required to determine the long term impact of the rotavirus immunisation programme.